Rare earth metal free hard magnet

JP2025023976AActive Publication Date: 2025-02-19MAX PLANCK GESELLSCHAFT ZUR FOERDERUNG DER WISSENSCHAFTEN EV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024192630
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-05-15
Filing Date
2024-11-01
Publication Date
2025-02-19
Estimated Expiration
2039-05-08

Smart Images

  • Figure 2025023976000002
    Figure 2025023976000002
  • Figure 2025023976000003
    Figure 2025023976000003
  • Figure 2025023976000004
    Figure 2025023976000004
Patent Text Reader

Abstract

To provide a hard magnetic material which does not contain rare earth metals but simultaneously exhibits high coercivity, high residual magnetism and high energy density.SOLUTION: An intermetallic compound has the following general composition of XaX'bYcZd. In the formula, X and X' are each independently a 3d transition metal with an unpaired electron, Y is a 4d or 5d transition metal of group 5, 8, 9 or 10, Z is a typical element of group 13, 14 or 15, a and d are each independently a number between 0.1 and 2.0, and b and c are each independently a number between 0.0 and 2.0, provided that a+b+c+d is between 3.0 and 4.0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to materials that contain permanent magnetic properties, also known as hard magnets. A good hard magnet or permanent magnet should generate a high magnetic field, should be able to withstand external forces that would demagnetize it, and should be mechanically strong. [Background technology]

[0002] Permanent magnetic materials play an important role in many areas of life, for example in medical diagnostics, magnetic circuits and spintronics.

[0003] Typically, hard magnetic materials are ferromagnetic materials characterized by high remanence and high coercivity.

[0004] If a ferromagnetic material is magnetized in one direction, it will not relax to zero magnetization when the applied magnetic field is removed. The amount of magnetization it retains with zero applied magnetic field is called remanence. To reverse the magnetization back to zero, a magnetic field in the opposite direction must be applied, and the amount of opposing magnetic field required for demagnetization is called coercivity. If an alternating magnetic field is applied to a material, its magnetization will follow a loop called a hysteresis loop. This hysteresis phenomenon is related to the existence of magnetic domains ("Weiss domains"). Some ferromagnetic materials will retain their applied magnetization almost indefinitely, and are therefore useful as "permanent magnets".

[0005] To be considered a potential permanent magnet, a magnetic material must have three intrinsic properties: - The Curie temperature (T C ), - Energy density (BH) max The saturation magnetization (Ms), which is crucial for - Anisotropy field B, which represents the upper limit of the potential coercivity of a permanent magnet a Uniaxial magnetocrystalline anisotropy, usually represented by is particularly important.

[0006] Currently, the most used high performance permanent magnets are made of samarium and cobalt (Sm-Co) and neodymium, iron and boron (Nd-Fe-B, e.g., NdFe 14 B) rare earth metal compound, the latter of which has a coercivity of about 1.2 T, a residual magnetization of about 1.2 T, and a maximum energy density (BH) of max Approximately 400kJm -3 However, dysprosium or praseodymium are required to improve corrosion stability and inherent coercivity. These rare earth elements are "strategic" due to their limited resources; their availability is subject to political constraints. Moreover, the sensitivity of these materials to corrosion limits their use to temperatures below 200 °C.

[0007] There are currently no real commercial alternatives to strong rare earth permanent magnets, as their magnetic properties make them superior to all previously known systems. Rare earth permanent magnets have high magnetic anisotropy, because the electrons in the f-shell are shielded from the ligand fields, and thus the orbital angular momentum of the shells shows its advantage. In addition, they can exhibit high local magnetic moments, allowing even higher saturation magnetization.

[0008] A rare earth metal-free alternative is ferrite, which can be manufactured on a large scale and typically has a high energy density (BH) max <40kJm -3 The use of ferrite is limited to applications that have low energy density, low cost, and a maximum operating temperature of 250°C.

[0009] Further alternatives are (BH) max Approximately 80kJm -3 Alnico magnets have a relatively high BH for rare earth metal-free alloys. max This is due to the high residual magnetism of about 1.1 T. Moreover, the coercive field strength μ0H of about 0.14 T Cis relatively small, which means that Alnico magnets have a risk of irreversible loss even at small field strengths. In addition, the bulk material is very brittle and therefore mechanically weak. However, their high service temperature of up to 550°C is a considerable advantage.

[0010] MnAl magnets currently have a Curie temperature of about 280°C, (BH) max Approximately 60kJm -3 Their remanence and coercivity reach 0.1μM. r Approximately 0.6T and μ0H C equivalent to about 0.4 T. They do not contain any "critical" elements and are therefore relatively cheap. Furthermore, they have a density of about 5 gcm -3 And while they are also relatively lightweight, their coercive force, less than 0.5T, is quite small.

[0011] (BH) max Approximately 50kJm -3 Bulk and thin film forms of magnets can also be produced from MnBi, having the following: The hard magnetic properties of MnBi are due to the uniaxial symmetry of the hexagonal crystal structure, its out-of-plane magnetization and the strong spin-orbit coupling of the heavy Bi.

[0012] Binary compounds, such as CoPt or FePt, which crystallize in the tetragonal structure type L10, can exhibit a coercivity of 2 T. However, a high platinum content is economically disadvantageous.

[0013] In addition, some Heusler compounds are known to have hard magnetic properties. Heusler compounds are ternary intermetallic compounds of formula X2YZ or XYZ, where X and Y are usually transition metals and Z is a typical element, the latter also known as half-Heusler compounds. The class of Heusler alloys includes over 1000 compounds that can be ferromagnetic or ferrimagnetic, although the elements that make up the compound do not necessarily have this magnetic property. Members of the tetragonal family of Heusler compounds can exhibit high magnetocrystalline anisotropy due to their inherent uniaxial symmetry. Because tetragonal compounds are usually ferrimagnetic, they exhibit only low saturation magnetization and therefore low remanence.

[0014] In addition to further developing and improving rare earth permanent magnets, (BH) max 100~300kJm -3 Research into new systems that bridge the gap between ferrite and Nd-Fe-B, which is in the range of 0.1 to 1.0, is an important step for future technology. Summary of the Invention [Problem to be solved by the invention]

[0015] It is therefore an object of the present invention to provide a hard magnetic material which does not contain rare earth metals, yet simultaneously exhibits high coercivity, high remanence and high energy density (compared to known non-rare earth metal-containing hard magnets). [Means for solving the problem]

[0016] The above problem is general composition X a X' b Y c Z d [In the formula, X and X' represent 3d transition metals with high total spin, i.e., unpaired electrons, e.g., Mn, Fe, Co, Ni; Y is a 4d or 5d transition metal of groups 5, 8, 9, or 10 characterized by high spin-orbit coupling (SOC), such as Ru, Rh, Pd, Pt, Ir, Ag, Au, Nb, or Ta; Z is a typical element of group 13, 14 or 15, such as Al, Ga, In, Ge, Sn, As, Sb or Bi, the higher homologues of these elements (In, Sn, Sb or Bi) are also characterized by high spin-orbit coupling (SOC); a and d represent numbers between 0.1 and 2.0; b and c represent numbers between 0.0 and 2.0; a+b+c+d shall be between 3.0 and 4.0. This problem is solved by rare earth metal-free ternary intermetallic compounds with hexagonal or trigonal symmetry.

[0017] So, in total, X a X' b Y c Z d represents an intermetallic compound whose composition lies between the Heusler and half-Heusler compounds.

[0018] These new compounds are characterized by high uniaxial magnetocrystalline anisotropy and therefore they are suitable for the production of rare-earth-free permanent magnetic materials with high coercive fields. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 shows room temperature powder X-ray diffraction patterns of 22 nm thin Mn1.5PtGa and 44 nm thin Mn1.08Fe0.58Pt1.19Ga layers grown on the (001) surface of a sapphire substrate (Al2O3) at different temperatures: a) 200°C; b) 300°C; c) 400°C; d) 300°C. [Diagram 2]a) Temperature dependence of magnetization upon cooling and at 0.05 T for a thin layer of Mn1.5PtGa on sapphire (001) as substrate; b) Out-of-plane (OP) and in-plane (IP) hysteresis curves at 20 K; c) Out-of-plane (OP) and in-plane (IP) hysteresis curves at 200 K; d) Out-of-plane hysteresis curves of a 22 nm thin Mn1.5PtGa layer deposited on a sapphire substrate at various temperatures (20, 50, 100, 150 and 200 K). [Diagram 3] a) Temperature dependence of magnetization upon cooling and in an external magnetic field of 0.1 T; b) Out-of-plane (OP) hysteresis curves at 50 K and 300 K for a 44 nm thick thin layer of MnFePtGa applied at 300 °C on a sapphire (001) carrier. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The ternary intermetallic compounds according to the present invention have a hexagonal or trigonal crystal structure. This symmetric crystal structure meets the criteria of crystal anisotropy due to its inherent uniaxial symmetry, which is an important feature. In the compounds of the present invention, this crystal anisotropy combines the obvious spin-orbit coupling of 4d and 5d elements (transition metals or main group elements). As a result, these compounds show strong magnetic anisotropy due to magnetocrystalline anisotropy even in the absence of shape anisotropy.

[0021] The intermetallic compound of the present invention has a general composition X a X' b Y c Z d and thus lies compositionally between Heusler and half-Heusler compounds.

[0022] Heusler compounds are intermetallic compounds of general composition X2YZ that crystallize in the L21 structure type (Pearson's Handbook of Crystallographic Data for Intermetallic Phases, ASM International,The Materials Information Society, 1991). Intermetallic compounds are generally a) Between two or more true metals (T1 and T2) b) Between one or more true metals and one or more true metals of subgroup B c) Between two or more metals of subgroup B It is a compound of the formula:

[0023] The properties of these compounds become less metallic and more similar to real compounds as we move from a) to c). The classification of the elements into true metals and subgroup B was first proposed by Walter R. Adapted from Table 13.1 in The Journal of the American Chemical Society (1976, p. 276).

[0024] [Table 1]

[0025] The lanthanide and actinide series metals belong to class T2. In the Heusler compounds X2YZ, X and Y are primarily transition metal elements (T2 in the table above), and sometimes Y is also a rare earth element. Z is a nonmagnetic metal or nonmetal (B1 or B2).

[0026] The intermetallic compound of the present invention has a general composition X a X' b Y c Z d In each of these Heusler and half-Heusler compounds, X and X' represent 3d transition metals with high total spin, i.e., with unpaired electrons, preferably Mn, Fe, Co or Ni; Y is a 4d or 5d transition metal of group 5, 8, 9, or 10, which metal is characterized by high spin-orbit coupling (SOC), preferably Ru, Rh, Pd, Pt, Ir, Ag, Au, Nb, or Ta; Z is a typical element of group 13, 14 or 15, preferably Al, Ga, In, Ge, Sn, As, Sb or Bi, the higher homologues of these elements (In, Sn, Sb or Bi) are also characterized by high spin-orbit coupling (SOC); a and d represent numbers between 0.1 and 2.0; b and c represent numbers between 0.0 and 2.0; However, a+b+c+d must be between 3.0 and 4.0.

[0027] In the Heusler compounds of the present invention, the parameters a, b, c and d can be independently selected from numbers between 0.1 and 2.0 (for a and d) and numbers between 0.0 and 2.0 (for b and c). Preferably a is 1 or 2, more preferably when b is 1, a is 1, and when b is 0, a is 2. Preferably d is 1. Preferably b is 0, or when a is 1, b is preferably 1. Preferably c is 1.

[0028] Generally, the sum of a, b, c and d is between 3.0 and 4.0, preferably 3.0 or 4.0.

[0029] Method of production For the production of the compounds of the invention, the sputtering technique is used. This allows the production of thin layers (films) of the compounds. For this purpose, elemental metals and / or alloys of two metals are used as targets in sputtering. The base pressure of the vacuum receiver is preferably 10 -6 mbar or less, more preferably 10 -7 mbar or less, most preferably 10 -8 mbar and the deposition is 0.1×10 -3 mbar~10×10 -3mbar, more preferably 1×10 -3 mbar~5×10 -3 mbar, most preferably 3×10 -3 The deposition is preferably carried out at a preferred temperature range of 100°C-500°C, more preferably 150°C-450°C, most preferably 200°C-400°C at 1000 psi and 1000 psi mbar. The growth rate of the thin layer is about 0.03-0.04 nm / s. After deposition, the thin layer on the substrate in the recipient is preferably vacuum annealed, preferably for 5-25 minutes, more preferably 10-20 minutes, most preferably about 15 minutes, and then slowly cooled to room temperature. A protective layer of aluminum, preferably 2-3 nm, is then deposited to precoat the thin metal layer to protect it from oxidation.

[0030] By modifying the deposition parameters, the crystal structure of the deposited material can be influenced. It was found that at low deposition temperatures of about 200° C., hexagonal structures are preferentially formed, while increasing the temperature (to about 400° C.) increases the proportion of tetragonal half-Heusler compounds. In a further preferred embodiment, the compounds can be obtained by epitaxial growth of thin films on a given substrate with the desired crystal structure, for example a sapphire substrate (along 0001) or on MgO (along 001) as substrate. It was observed that the hexagonal compounds of the invention grow preferentially on sapphire, with the crystallographic 0001 direction perpendicular to the substrate surface. In principle, hexagonal Ru or Co can also be used as substrate surface. However, these substrates have a high lattice mismatch compared to the hexagonal compounds of the invention and are therefore less preferred. Further, but still less preferred, options are hexagonal SiC(2H) and trigonal SiO2 as substrates, thin layers grown on these types of substrates showed poorer crystallinity.

[0031] Manufacturing magnets for use For use as magnets, the compounds of the invention can be sintered, for example, as raw materials, or bonded with a suitable binder material. Sintered magnets are usually strong and anisotropic, but limited in shape. They are made by pressing the raw materials, followed by a heating process. Bonded magnets are not as strong as sintered ones, but are less expensive and can be made in almost any size and shape. For bonded magnets, the raw materials (compounds according to the invention) are mixed with 5-90% by weight, preferably 10-60% by weight, more preferably 20-40% by weight of a binder, compressed and cured at high temperature (for example, 50-350°C, preferably 80-280°C, more preferably 100-200°C, depending on the temperature stability of the binder and magnetic compound used). They are isotropic, i.e., they can be magnetized in any direction. The molding process can be, for example, an injection molding or compression bonding process. Typical binder types are nylon, polyamide, polyphenylene sulfide (PPS) and nitrile butadiene rubber (NBR). EXAMPLES

[0032] Equipment and Measurement Method The crystal structure and film thickness are CuK α The materials were tested by X-ray diffraction (XRD) measurements using a Philips PANanalytical X'pert Pro source. To determine the composition of the films, energy dispersive X-ray spectroscopy (EDX) measurements were performed using QUANTA The measurements were performed at 200 FEG I. The film thickness was obtained using the StrataGEM software package. A Quantum Design Superconducting Quantum Interference Device Vibrating Sample Magnetometer (MPMS-3) was used to study the magnetic properties of the thin films.

[0033] Example 1 and Example 2 Mn 1.5 PtGa and Mn 1.08 Fe 0.58 Pt 1.19 Ga Mn 1.5 PtGa and Mn1.08 Fe 0.58 Pt 1.19 A thin layer of Ga was produced by epitaxial growth on a sapphire surface (0001) as a substrate. Since sapphire (Al2O3) crystallizes in the trigonal crystal system, i.e. with hexagonal metric, the structure of the sapphire surface is dominated by Mn 1.5 PtGa and Mn 1.08 Fe 0.58 Pt 1.19 Supports epitaxial growth of Ga layers.

[0034] The elements manganese, platinum, iron and an alloy of composition MnGa were used as sputtering targets. The base pressure of the vacuum receiver was 10 -8 mbar, and the deposition on the substrate is 3×10 -3 The deposition was performed at a pressure of 1000 psi and a temperature range of 200°C to 300°C. The growth rate of the thin layer was about 0.03-0.04 nm / s. After deposition, the thin layer on the substrate in the recipient was vacuum annealed for 15 min and then slowly cooled to room temperature. A protective layer of 2-3 nm of aluminum was then deposited to protect the thin metal layer from oxidation.

[0035] Mn 1.5 A 22 nm thin layer of PtGa and Mn 1.08 Fe 0.58 Pt 1.19The powder X-ray diffraction pattern at room temperature for a 44 nm thin layer of Ga in the "out-of-plane" geometry is shown in Figure 1. The Bragg reflections of the hexagonal structure are labelled H(0002) and H(0004). The thin layer grown at 300 °C (Figure 1b) shows a better crystallinity compared to the layer applied at 200 °C (Figure 1a). At deposition temperatures above 300 °C (Figure 1c), a decrease in the Bragg intensity and additional weak reflections (marked with *) were observed. The additional reflections can be considered to be caused by a tetragonal half-Heusler compound as a second phase. A similar behaviour was observed in the bulk sample. Partial substitution of Mn by Fe maintains the hexagonal structure, as shown in Figure 1d. All thin films deposited on sapphire (0001) show texture, regardless of the temperature of deposition. The hexagonal Mn is formed by epitaxial growth on the surface of the trigonal substrate. 1.5 PtGa and Mn 1.08 Fe 0.58 Pt 1.19 The Ga was deposited with a preferred orientation in the crystallographic

[0001] direction perpendicular to the surface of the substrate, and thus parallel to the crystallographic c-axis of sapphire, respectively.

[0036] The crystal structure of the deposited material can be influenced by different deposition parameters. It has been observed that at low deposition temperatures, the hexagonal structure is preferentially formed, while with increasing temperature, the proportion of tetragonal half-Heusler compounds increases. The lattice parameters of the hexagonal structure are 1.5 For PtGa, a = 4.35 Å and c = 5.58 Å, for Mn 1.08 Fe 0.58 Pt 1.19 For Ga, a = 4.33 Å and c = 5.52 Å. This corresponds to a lattice mismatch of about 8.2% and 8.6% with respect to the a-axis of the sapphire substrate, a = 4.74 Å. Despite the relatively large lattice mismatch, the Mn 1.5 PtGa and Mn 1.08 Fe 0.58 Pt 1.19 Epitaxial growth of Ga was observed.

[0037] Mn deposited on a sapphire (0001) surface at 300℃ 1.5 The magnetic properties of well-crystalline thin layers of PtGa are shown in Figure 2. Figure 2a shows the magnetization as a function of temperature, measured in field-cooled mode (FC) at a field strength of 0.05 T. The Curie temperature (T C ) where the phase transition from ferromagnetism to paramagnetism occurs was observed. The corresponding M(H) curves for 20 K and 200 K are shown in Fig. 2b and Fig. 2c for the "in-plane" (IP) and "out-of-plane" (OP) directions, respectively. The data shown correspond to the raw data after subtraction of the substrate contribution for the respective temperature. At 20 K, in the "out-of-plane" orientation, the sample shows a coercive field strength Hc of 1.5 T, but at 200 K, it shows only a nearly vanishing coercivity (0.18 T) (due to the temperature dependence of the magnetic anisotropy). Fig. 2d shows a systematic decrease of the coercivity with increasing temperature. The measurements of the coercivity in the "out-of-plane" direction show a stronger magnetic anisotropy compared to the "in-plane" measurements. At 20 K and 5 T, a total magnetization of 400 kA / m was measured. This corresponds to the formula K U =(μ0M S ×H a ) / 2 anisotropy constant (K U ) is 3.3MJ / m 3 Bring about. M S is the saturation magnetization and Ha is the anisotropy field. An estimate of the latter is obtained by using the intersection of the "in-plane" and "out-of-plane" plots. Mn 1.5 A thin layer of PtGa at 20K (BH) max Approximately 30kJm -3 As the temperature increases, (BH) max decreases, and at 200 K, i.e., near the Curie temperature, it is only 4 kJm -3 It was.

[0038] Figure 3 shows the Mn deposited at 300°C. 1.08 Fe 0.58 Pt 1.19The magnetization as a function of temperature (Fig. 3a), measured in field cooling mode (FC) at a field strength of 0.1 T, shows a ferromagnetic to paramagnetic phase transition at about 312 K. Hysteresis curves measured at 50 K and 300 K in the out-of-plane geometry are shown in Fig. 3b, respectively. The low-temperature measurements show a coercive field strength of 0.87 T, while T C A nearby measurement was 0.02T.

[0039] Both examples illustrate that materials with a hexagonal crystal structure can exhibit significant coercivity and remanence in the presence of elements with sufficient unpaired electrons, such as manganese or iron, and elements with pronounced spin-orbit coupling, such as platinum. 1.08 Fe 0.58 Pt 1.19 The Ga system also shows that it is possible to further increase both the Curie temperature and the magnetic moment in a quaternary system. Similar results can be achieved in the MnCoPtGa system.

Claims

1. A hard magnet having a general composition X a X' b Y c Z d [In the formula, X and X′, independently of each other, represent a 3d transition metal having an unpaired electron; Y is a 4d or 5d transition metal of Group 5, 8, 9, or 10; Z is a Group 13, 14 or 15 element; a and d independently represent a number between 0.1 and 2.0; b represents a number between 0.0 and 2.0; c is 1; However, a+b+c+d is between 3.0 and 4.

0. The hard magnet comprises an intermetallic compound having the formula:

2. 2. The hard magnet of claim 1, wherein X and X' are independently selected from Mn, Fe, Co or Ni.

3. 3. The hard magnet according to claim 1, wherein Y is Ru, Rh, Pd, Pt, Ir, Ag, Au, Nb or Ta.

4. 4. The hard magnet according to claim 1, wherein Z is Al, Ga, In, Ge, Sn, As, Sb or Bi.

5. a is 1 or 2, more preferably when b is 1, a is 1; if b is 0 then a is 2; The hard magnet according to any one of claims 1 to 4.

6. The hard magnet according to any one of claims 1 to 5, wherein d is 1.

7. b is 0, or if a is 1 then b is 1; The hard magnet according to any one of claims 1 to 6.

8. The hard magnet according to any one of claims 1 to 7, wherein the sum of a, b, c and d is 3.0 or 4.

0.

9. A hard magnet according to any one of claims 1 to 8, wherein the intermetallic compound has hexagonal or trigonal symmetry.

10. 10. The hard magnet according to claim 1, wherein the intermetallic compound has magnetocrystalline anisotropy.

11. 11. The hard magnet according to claim 1, having a coercive force Bc of 0.05 T or more.

12. A hard magnet according to any one of claims 1 to 11, which is sintered.

13. The hard magnet of any one of claims 1 to 11, further comprising a binder.

14. General composition X a X' b Y c Z d [In the formula, X and X′ represent 3d transition metals having unpaired electrons; Y is a 4d or 5d transition metal of Group 5, 8, 9, or 10; Z is a Group 13, 14 or 15 element; a and d independently represent numbers between 0.1 and 2.0; b and c independently represent numbers between 0.0 and 2.0; However, a+b+c+d is between 3.0 and 4.

0.

2. Use of an intermetallic compound having the formula:

Citation Information

Patent Citations

  • Magneto-optical material

    JP1988079253A

  • Magneto-optical recording medium and its production

    JP1995272334A

  • Perpendicular magnetic recording medium and its production

    JP1998275320A

  • R-t-b-based permanent magnet

    JP2014216463A

  • Rare earth metal-free hard magnets

    JP2021523576A